Targeting immunoproteasome and glutamine supplementation prevent intestinal hyperpermeability - Ghouzali, Ibtissem; Lemaitre, Caroline; Bahlouli, Wafa; Azhar, Saïda; Bôle-Feysot, Christine; Meleine, Mathieu; Ducrotté, Philippe; Déchelotte, Pierre; Coëffier, Moïse (Biochimica et biophysica acta. General subjects, 2017)
Intestinal hyperpermeability has been reported in several intestinal and non-intestinal disorders. We aimed to investigate the role of the ubiquitin proteasome system in gut barrier regulation in two mice models: the water avoidance stress model (WAS) and a post-inflammatory model (post-TNBS). Both models were applied in C57BL/6 male mice (n=7–8/group); Proteasome was targeted by injection of a selective proteasome inhibitor or by using knock-out mice for β2i proteasome subunit. Finally, glutamine supplementation was evaluated. In both models (WAS at day 10, post-TNBS at day 28), we observed an increase in proteasome trypsin-like activity and in inducible β2/constitutive β2 subunit protein expression ratio, associated with an increase in intestinal permeability. Moreover, intestinal hyperpermeability was blunted by intraperitoneal injection of selective proteasome inhibitor in WAS and post-TNBS mice. Of note, knock-out mice for the β2i subunit exhibited a significant decrease in intestinal permeability and fecal pellet output during WAS. Glutamine supplementation also improved colonic permeability in both models. In conclusion, the proteasome system is altered in the colonic mucosa of WAS and post-TNBS mice with increased trypsin-like activity. Associated intestinal hyperpermeability was blunted by immunoproteasome inhibition. •Ubiquitin Proteasome System is altered in the colon mucosa of stressed mice.•Ubiquitin Proteasome System is altered in the colon post-inflammatory mucosa.•Targeting immunoproteasome by pharmacological or genetic approaches prevents intestinal hyperpermeability.•Intestinal hyperpermeability is limited by glutamine.